Localisation of Abundant and Organ-Specific Genes Expressed in Rosa hybrida Leaves and Flower Buds by Direct In Situ RT-PCR - Agata Jedrzejuk; Heiko Mibus; Margrethe Serek (The Scientific World Journal)
In situ PCR is a technique that allows specific nucleic acid sequences to be detected in individual cells and tissues. In situ PCR and IS-RT-PCR are elegant techniques that can increase both sensitivity and throughput, but they are, at best, only semiquantitative; therefore, it is desirable first to ascertain the expression pattern by conventional means to establish the suitable conditions for each probe. In plants, in situ RT-PCR is widely used in the expression localisation of specific genes, including MADS-box and other function-specific genes or housekeeping genes in floral buds and other organs. This method is especially useful in small organs or during early developmental stages when the separation of particular parts is impossible. In this paper, we compared three different labelling and immunodetection methods by using in situ RT-PCR in Rosa hybrida flower buds and leaves. As target genes, we used the abundant β-actin and RhFUL gene, which is expressed only in the leaves and petals/sepals of flower buds. We used digoxygenin-11-dUTP, biotin-11-dUTP, and fluorescein-12-dUTP-labelled nucleotides and antidig-AP/ streptavidin-fluorescein-labelled antibodies. All of the used methods gave strong, specific signal and all of them may be used in localization of gene expression on tissue level in rose organs.